PEMAHAMAN MAKNA HIJAB VAPERS DALAM MENGGUNAKAN VAPE - Bagus Dwi Bramantyo; Christiana Wulandari (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Vape is one example of the success of the results of technological developments in the field of e-cigarettes. At this time, vape users did not only come from men, but women had also become vape users, even among women wearing the hijab. The purpose of this study was to determine the understanding of the motives of women wearing hijabs in using a vape. This study uses a phenomenological method with a qualitative approach and based on an interpretive paradigm. This research uses George Kelly's Personal Construct theory to explain a person's picture of the world around him that has been obtained based on his involvement and interpretation of his life. The results of this study indicate that the meaning given to women wearing hijab is inseparable from their experience of wanting to quit conventional cigarettes and their desire to become an influencer in vaping activities. Also, they said that doing vaping activities and continuing to practice their belief in wearing the hijab was the main essence for him as a hijab vapers. For them, giving the same meaning to the hijab and vape makes does not make sense.